(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2008)
Main results of corresponding member of the Bulgarian Academy of Sciences Professor Dolapchiev in the field of Analytical Mechanics concerning motion equations are presented. They are based on the variational principles of mechanics and can be applied to both holonomic and nonholonomic systems.